Systematics and taxonomy of Pipistrellus kuhlii (Kuhl, 1817) in Central Europe and the Balkans - Sachanowicz, Konrad; Piskorski, Michał; Tereba, Anna (Zootaxa, 2017)
We examined selected external characteristics and measurements of Pipistrellus k. kuhlii and P. k. lepidus representatives from the Balkans and Central Europe, whose ranges have rapidly expanded over the past few decades. We also sequenced and analysed two mitochondrial (16S and COI genes) and one nuclear (RAG2) markers of these two bat morphotypes to determine haplotype diversity and distribution patterns with a wider geographic perspective. We found that bats of the two taxa differed markedly with regard to the overall body coloration, size (P. k. lepidus is larger than P. k. kuhlii), extent and shape of the pale wing margin, and penis coloration, a finding which seems to be of diagnostic value, similarly to other Pipistrellus species. No polymorphism in RAG2 marker was found, but in both mtDNA markers we detected different haplotypes characteristic for both taxa, corresponding to morphological and morphometric patterns established in this study. Our genetic analysis results confirmed a clear division into two phylogenetic lineages and may indicate their allopatric speciation and a very recent simultaneous expansion to the Balkans and Central Europe from the Mediterranean region (P. kuhlii/deserti) and south-west Asia across eastern Europe (P. k. lepidus). We also show that P. k. lepidus distribution is wider than previously reported, and that the ranges of P. k. lepidus and P. k. kuhlii have already contacted in Central Europe.